Соціокультурна мотивація і прагматичне варіювання висловлення-подяки в англійському діалогічному мовленні - Чарікова, Ірина Василівна; Charikova, I. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено проблему соціокультурної та прагматичної мотивації вживання висловлення-подяки в англійському діалогічному мовленні. Визначено почуття вдячності та принцип ввічливості як основні складники етико-психологічного змісту висловлення-подяки. Встановлено, що вибір комунікативної стратегії зумовлюється конвенціями ввічливості, які відповідають соціокультурним нормам та правилам комунікації. Як одна з найбільш важливих етикетних формул, подяка зафіксована в типових соціокультурних ситуаціях і належить до стратегій позитивної ввічливості. The article addresses socio-cultural motivation and pragmatic variation of thanks-utterance in the English speech. Feeling of gratitude and politeness principle are defined as the main components of ethic and psychological content of thanks-utterance. Awareness of the factors of the usage of this utterance – semantic, socio-pragmatic and interactional are express conditions of its effectiveness in communication. The choice of communicative strategies is determined by conventions of politeness that corresponds to socio-cultural norms and rules of communication. Being one of the most important speech etiquette rituals, thanks-utterance is fixed in typical socio-cultural situations and belongs to positive politeness strategies. Despite commonality of the discourse events containing thanks-utterances, degree of the ritualization varies depending on the contexts of their usage.
Socio-cultural Motivation and Pragmatic Variation of Thanks-Utterance in the English Speech
Keywords: комунікація; communication; прагматика; pragmatics; авторська інтенція; author’s intention